The Rationale for Helping Teacher Candidates Integrate Self-reflection into Chaotic Schedules - Sarah Y.S Tham (The Advocate, 2021)
There is no doubt that teachers want to self-reflect. However, given the increasing number of teachers' responsibilities in and out of the classroom, teachers have to set priorities. In teacher education programs, self-reflection is included but often not emphasized. Teacher candidates are encouraged to reflect on their lesson plans, study materials, writing, and teaching experience, but a structured and useable framework is often lacking. In the end, instruction, assessments, diagnosis, and interventions remain at the forefront of teachers' minds, and self-reflection is put on the burner. This paper presents findings of how self-reflection influenced tutors in the classrooms they were tutoring in and suggests that Korthagen's (1985) framework could help teacher candidates and even classroom teachers begin integrating self-reflection into their busy schedules. As teachers continue an era of virtual classrooms, having a workable self-reflection framework might be the extra edge they need presently
Keywords: Self-reflection; teacher education programs; teacher candidates; ALACT